Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.psychres.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of first-episode unipolar major depression in individuals with and without sub-threshold depressive symptoms: A prospective, population-based study

Abstract: Background The aim of this study is to assess predictors of first-episode major depression in a community-based sample of adults with and without sub-threshold depression. Method Data were from Waves 1 & 2 of the National Epidemiological Survey on Alcohol and Related Conditions (NESARC). Participants meeting criteria for a sub-threshold depressive episode (sMDE; n = 3,901) reported lifetime depressed mood/loss of interest lasting at least two weeks and at least two of the seven other DSM-IV symptoms of MDD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
0
6
0
1
Order By: Relevance
“…Of the 16 studies, 10 used a case definition corresponding with the diagnostic criteria for minor depression (Bruce & Hoff, 1994; Wagner et al 2000; Lyness et al 2002; Cuijpers et al 2004; Forsell, 2007; Jackson et al 2007; Johnson et al 2009; Shankman et al 2009; Peters et al 2015; McLeod et al 2016), three involved experiencing 2–4 depressive symptoms (Horwath et al 1992; Crum et al 1994; Oldehinkel et al 1999) and three involved having elevated scores on a depression rating scale (Beekman et al 2002; Jonsson et al 2011; Jinnin et al 2017). Most studies ( N = 15) used structured clinical interviews that identified cases of major depression based on DSM-III or DSM-IV criteria (Horwath et al 1992; Bruce & Hoff, 1994; Crum et al 1994; Oldehinkel et al 1999; Wagner et al 2000; Beekman et al 2002; Lyness et al 2002; Cuijpers et al 2004; Jackson et al 2007; Johnson et al 2009; Shankman et al 2009; Jonsson et al 2011; Peters et al 2015; McLeod et al 2016; Jinnin et al 2017), with one study by Forsell (2007) using a self-report questionnaire to identify cases of major depression that meet DSM-IV diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 16 studies, 10 used a case definition corresponding with the diagnostic criteria for minor depression (Bruce & Hoff, 1994; Wagner et al 2000; Lyness et al 2002; Cuijpers et al 2004; Forsell, 2007; Jackson et al 2007; Johnson et al 2009; Shankman et al 2009; Peters et al 2015; McLeod et al 2016), three involved experiencing 2–4 depressive symptoms (Horwath et al 1992; Crum et al 1994; Oldehinkel et al 1999) and three involved having elevated scores on a depression rating scale (Beekman et al 2002; Jonsson et al 2011; Jinnin et al 2017). Most studies ( N = 15) used structured clinical interviews that identified cases of major depression based on DSM-III or DSM-IV criteria (Horwath et al 1992; Bruce & Hoff, 1994; Crum et al 1994; Oldehinkel et al 1999; Wagner et al 2000; Beekman et al 2002; Lyness et al 2002; Cuijpers et al 2004; Jackson et al 2007; Johnson et al 2009; Shankman et al 2009; Jonsson et al 2011; Peters et al 2015; McLeod et al 2016; Jinnin et al 2017), with one study by Forsell (2007) using a self-report questionnaire to identify cases of major depression that meet DSM-IV diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents a summary of study design factors for the 16 cohort studies included in the meta-analysis. Of the 16 studies, six involved community-based adult samples ( n = 57 813) (Horwath et al 1992; Bruce & Hoff, 1994; Cuijpers et al 2004; Forsell, 2007; Peters et al 2015; Jinnin et al 2017), five involved community-based youth samples ( n = 4136) (Oldehinkel et al 1999; Johnson et al 2009; Shankman et al 2009; Jonsson et al 2011; McLeod et al 2016), three involved primary care adult samples ( n = 4540) (Crum et al 1994; Wagner et al 2000; Jackson et al 2007), one involved a community-based elderly sample ( n = 604) (Beekman et al 2002) and one involved a primary care elderly sample ( n = 225) (Lyness et al 2002). The average starting age of study participants ranged between 15.0 and 16.6 years in youth samples, 18.3 and 58.9 years in adult samples and 71.1 and 71.8 in elderly samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Дослідження особливостей сучасної клінічної феноменології депресивних розладів на ініціальному етапі має важливе значення для розуміння закономірностей та динаміки клінічного патоморфозу депресій, а результати таких досліджень можуть бути покладені в основу розробки сучасних методів прогнозування, лікування та профілактики депресивних розладів [9,10]. Особливо цінними є результати аналізу предикторів первинного епізоду депресивного розладу, оскільки це дає можливість передбачати виникнення захворювання і спрямовувати зусилля на його первинну профілактику; при цьому сьогодні відчувається брак таких досліджень і недостатність інформації щодо преморбідної та ініціальної симптоматики депресій, асоційованої з високим ризиком розвитку афективної патології [11].…”
Section: деякі предиктори депресивних розладів у контексті клінічного патоморфозуunclassified
“…Such mild depression is associated with significant personal and public health consequences [ 4 ] and is a strong predictor for future onset of full [ 5 ]. Sub-threshold depression has a lifetime prevalence rate of 26% [ 6 ] and about 30% of affective disorders that occur in adulthood start in adolescence [ 7 ]. Depression in adolescence predicts a range of adverse outcomes in adulthood, including ongoing mental health problems [ 8 ], poorer physical health [ 9 ], and social, legal and financial problems [ 10 ], and is the most prevalent psychiatric disorder in young people who die by suicide [ 11 ].…”
Section: Introductionmentioning
confidence: 99%